PENGEMBANGAN MODEL PEMBINAAN DISIPLIN YANG EFEKTIF TERHADAP KINERJA PEGAWAI NEGERI SIPIL - Herman Herman (Jurnal Manajemen Kepegawaian, 2008)
The discipline of civil servant has long been an intersting topics to continously discuss, in particular in discussions of the civil servant development. Normatively, the discipline of civil servants have been regulated, yet the rules and regulation number 30 year 1980 on Discipline of Civil Servant, still limited on obligations, restrictions and sanctions. However, the methods how to develop them is not regulated yet. This is important became discipline can not be instilled in short time, but it requires well planned, continous, and systematic development to achieve ideal civil servants. The model presented in this article is expected to be utilized as refference for helping the leaders in every levels to develop discipline of the service servants in organization.Key words: development, discipline, and civil servant